Simulation of Control Cascaded Boost Converter Series Connected and Applied in Electric Motor as Prime Mover of Irrigation Water Pump - Soedibyo, Soedibyo; Ashari, Mochamad (JAVA Journal of Electrical and Electronics Engineering, 2016)
Abstract— The purpose of this paper is to achieve the system design that can supply energy from solar PV to the water pump irrigation motor. This research focused on design system of boost converter cascade series connected. Battery charging process and load supply is taken in the same time when the sun irradiation still exist. Power plant supply the power to the motor load with the capacity 2 HP, 90% efficiency, 380 Volt 3-phase. Inverter power rating is 1,750 Watt with the input voltage is 650 Volt-dc. Terminal voltage of inverter is 380 Volt-ac, 3-phase. Pump operate within ten hours during daylight and fourteen hours during day night. Terminal voltage from the first converter is about 114 Vdc and the second converter is about 650 Vdc. Batteries used is 3 x 12 V in series connected with the capacity of 40 Ah for each battery. Output power that produced from PV is controlled by first stage boost converter that has function to supply the power to the boost converter_2 circuit to achieve the Maximum Power Point (MPP). Controller is used for rising the efficiency of MPP. From the output boost converter_2 terminal, it’s connected to inverter that convert output DC voltage from the boost converter_2 to AC voltage 380 V, 3-phase and 50 Hz. Design of system model is simulated in MATLAB software. The result of simulation shows the scheme proposed could supply the power to energize the motor of water pump within 24 hours.